KONSELING SINGKAT BERFOKUS SOLUSI UNTUK MENINGKATKAN ORIENTASI MASA DEPAN PADA BIDANG PENDIDIKAN - Dewa Ayu Eka; Elly Nurhayati (HUMANITAS: Indonesian Psychological Journal, 2015)
AbstractThe aim of this study is to improve the future of education orients in adolescents. The data were obtained through the future–oriented scale of education, interview and observation. The interventions used are solution-focused brief counseling (KSFS). The intervention was conducted six meetings, each of which was done three times a week. The subjects of the study were all the seventh and ninth graders of SMP 4 Pandak, Bantul, which totaled 214 students. The subjects were given a screening as the pretest with the results of 64 students in the medium future-oriented category of education. The results of the pretest were performed randomly to get the two groups, i.e. 10 students as the experimental group and 10 students as a control group. Data were analyzed using the Mann-Whitney test and Wilcoxon technique. Results showed that z Z score coefficient reach z=- 2.02 with p = 0,043 (p<0,05, it means that there was significantly high differences in the future-oriented education between the control group and experimental group after given a brief counseling intervention focused solutions. Planning aspect gave the highest contribution for increasingstudents, future orientation compared to motivation and evaluation.Key words: brief counseling focused on solution, counseling, future orientation,